The model for evaluating the criteria describing the quality of the trip by international train - Maskeliūnaitė, Lijana; Sivilevičius, Henrikas (Technological and Economic Development of Economy, 2014)
The quality of multifaceted objects or phenomena can be hardly described or evaluated by a single criterion. The quality of the trip by train is described by a set of quantitative and qualitative criteria. The influence of all the criteria on the trip by international train may be evaluated by a comprehensive quality index (CQI) or quality index K. An additive model is offered for calculating CQI, which consists of the average weights of the criterion groups, as well as normalized weights and variables of the criteria, showing the correspondence of the real value of each criterion to the best, critical or allowable value. A mathematical model, which may be used for determining the quality of the trip by train based on the criteria describing the elements of the train and technical state of the railway track is also presented. Based on the use of 16 criteria describing the elements of the train and the parameters and the technical state of the railway track, the quantitative estimate KA (multiple criteria index) is obtained. The suggested model and the techniques used in the work may be applied to determining the quality or effectiveness of other objects or processes, which can be described by sets of criteria.